Survey of petroleum hydrocarbons bioremediation in aquatic environment - Mohajeri, L. (2005)
Crude oil is one of the most important organic pollutants in aquatic ecosystems. One of the best skills for treatment of the marine and coastal environments is bioremediation “the use of microorganisms to accelerate the degradation of environmental contaminants”. It is a cost effective, green and safe technology. It is estimated that under natural conditions it would be five to ten years before natural conditions are achieved, with bioremediation this would be possible in two to three years. This research evaluates techniques to improve bioremediation in tropical marine environments. Approaches for improving microbial degradation of crude oil are discussed. The survey shows that concentrations of available nitrogen and phosphorous in seawater are the main limiting factors. In addition, temperature and oxygen are limiting factors in cold and tropical waters respectively. The concepts of bioavailability, factors influencing media as well as strategies for enhancing bioremediation are investigated in this research.